2018
DOI: 10.1111/dme.13793
|View full text |Cite
|
Sign up to set email alerts
|

Is insulin pump therapy effective in Type 1 diabetes?

Abstract: There continues to be uncertainty about the effectiveness in Type 1 diabetes of insulin pump therapy (continuous subcutaneous insulin infusion, CSII) vs. multiple daily insulin injections (MDI). This narrative review discusses the reasons for this uncertainty, summarizes the current evidence base for CSII and suggests some future research needs. There are difficulties in interpreting trials of CSII because effectiveness varies widely due to factors such as differing baseline control, suboptimal use of best CSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 49 publications
1
37
0
3
Order By: Relevance
“…Very few specific recommendations on use of new diabetes technologies for older individuals exist and there are no ‘official’ criteria to decide about discontinuation of CSII . Discontinuation rates for insulin pumps are generally low, because CSII is an effective treatment option for achieving and maintaining good glycaemic control in people with type 1 diabetes, and treatment satisfaction can be better compared with insulin injection therapy . A recent longitudinal analysis of the T1D Exchange Registry on pump discontinuation rates reported that discontinuation rates among adults aged ≥ 26 years were < 1% .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few specific recommendations on use of new diabetes technologies for older individuals exist and there are no ‘official’ criteria to decide about discontinuation of CSII . Discontinuation rates for insulin pumps are generally low, because CSII is an effective treatment option for achieving and maintaining good glycaemic control in people with type 1 diabetes, and treatment satisfaction can be better compared with insulin injection therapy . A recent longitudinal analysis of the T1D Exchange Registry on pump discontinuation rates reported that discontinuation rates among adults aged ≥ 26 years were < 1% .…”
Section: Discussionmentioning
confidence: 99%
“…Little is known, however, about the characteristics of adults aged ≥ 60 years using CSII. There are many studies examining the effectiveness and use of CSII in adults and children . However, research on the benefits of insulin pump use in older individuals with type 1 diabetes is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The design of the present study did not allow us to investigate causes for the observed association between insulin regimen and lipid profiles; however, the finding of a favourable lipid profile with pump therapy in this cross‐sectional analysis of registry data requires further investigation for potential mechanisms. It is possible that characteristics of children with access to pump therapy are different from those who do not access pump therapy, such as lifestyle factors, including healthier diet, smoking avoidance, regular exercise, socio‐economic status, more intensive education and stronger motivation, and these may all affect lipid profiles . These factors were not examined in the present study as they are not currently collected in the SWEET database.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of physical activity, when possible, and adequate diet, were acknowledged very early [28]. Most diabetes patients develop a need for drug treatment during the course of the disease, and there have been major developments in pharmacological, as well as technical, treatment the past two decades, with a number of new classes of glucose-lowering drugs becoming available, along with new types of insulins, and techniques for delivering insulin, that are beneficial at least to subgroups of patients [23,24,29]. The newest techniques for measuring glucose became more generally available after this study period, but it is reasonable to assume that all the factors mentioned have contributed to the improvements in prognosis and outcome now seen, where care is available, for the population with diabetes, despite that both incidence and prevalence of diabetes is still increasing in most regions, possibly with the exception of the northern western countries [9].…”
Section: Reasons For Improved Mortalitymentioning
confidence: 99%